Decreased IL‐10 expression in stefin B‐deficient macrophages is regulated by the MAP kinase and STAT‐3 signaling pathways. Issue 5 (23rd January 2014) - Maher, Katarina; Završnik, Janja; Jerič-Kokelj, Barbara; Vasiljeva, Olga; Turk, Boris; Kopitar-Jerala, Nataša
Abstract : Innate immune responses are tightly regulated to avoid excessive activation and subsequent inflammatory damage to the host, and interleukin‐10 (IL‐10) plays a crucial role in preventing inflammation. Stefin B (cystatin B) is an endogenous inhibitor of cysteine proteinases. In stefin B‐deficient bone marrow‐derived macrophages (BMDMs), we detected an increase in the induction of the LPS‐induced pro‐inflammatory signal nitric oxide (NO) but decreased IL‐10 expression. The phosphorylation of ERK and p38 MAP‐kinases was significantly decreased in stefin B‐deficient macrophages, as was STAT‐3 phosphorylation. These findings show that stefin B influences the expression of anti‐inflammatory IL‐10 in response to the TLR4 agonist LPS. Abstract : Stefin B expression is up‐regulated in activated macrophages. Stefin B‐deficient BMDMs secrete more NO than WT cells upon IFN‐γ and LPS activation. Stefin B‐deficient BMDMs express less IL‐10 than WT cells upon LPS stimulation. ERK and STAT3 play a role in lowering IL‐10 expression in stefin B‐deficient BMDMs.